Chitosan-bovine serum albumin complex formation: A model to design an enzyme isolation method by polyelectrolyte precipitation - Boeris, Valeria (2010)
Interactions between a model protein (bovine serum albumin-BSA) and the cationic polyelectrolyte, chitosan (Chi), have been characterized by turbidimetry, circular dichroism and fluorescence spectroscopy. It has been found that the conformation of the BSA does not change significantly during the chain interaction between BSA and chitosan forming the non-covalently linked complex. The effects of pH, ionic strength and anions which modify the water structure around BSA were evaluated in the chitosan-BSA complex formation. A net coulombic interaction force between BSA and Chi was found as the insoluble complex formation decreased after the addition of NaCl. Around 80% of the BSA in solution precipitates with the Chi addition. A concentration of 0.05% (w/v) Chi was necessary to precipitate the protein, with a stoichiometry of 6.9 g BSA/g Chi. No modification of the tertiary and secondary structure of BSA was observed when the precipitate was dissolved by changing the pH of the medium. Chitosan proved to be a useful framework to isolate proteins with a slightly acid isoelectrical pH by means of precipitation.